Efectos de la cobertura vegetal de charcos en afloramientos rocosos del escudo guyanés sobre la sucesión y diversidad funcional de macroinvertebrados acuáticos (2021)
The rock pools from the Guyana Shield are poorly studied ecosystems whose dynamics are associated to several biotic and abiotic variables that influence their hydroperiod and the complexity of their microhabitats. Aquatic macroinvertebrates (MIA) are organisms involved in process such as nutrient recycling and energy flow, which respond to specific environmental changes. Functional Feeding Groups (FFG) combine morphological characteristics and behavioral mechanisms to be close to the ecological function of organisms and thus understand the dynamics of the ecosystem. This study aims to see how abiotic and plant coverture variables influence the functional diversity of MIA, considering the ecological succession as a covariate. Physicochemical parameters of pools were analyzed in two ecological times: at the beginning and at the climax of the wet season. In addition, MIA samples were taken and classified according to their FFG...